Statistical lightning study for 33kV overhead line in peninsular Malaysia - Hatta N.M.; Abdullah N.; Osman M.; Abidin Ab Kadir M.Z. (Institute of Electrical and Electronics Engineers Inc., 2023)
Overhead lines; Probability distributions; Cumulative probability distribution curves; Ground flash densities; Lightning detection; Malaysia; Overhead distribution line; Peak currents; Statistical parameters; Statistical study; Lightning